Decentralization and Subnational Politics in North America - Ponce Rodríguez, Raul Alberto (Edward Elgar Publishing Limited, 2021)
This chapter reviews the relationship between subnational politics and decentralization in the United States, Mexico, and Canada. There is a significant contrast in fiscal and political institutions implemented in these countries: the US is fiscally and politically decentralized with direct democracy provisions that lead to important effects on taxation and spending of subnational governments. In comparison, Mexico is fiscally and politically centralized with a tax revenue sharing accord that creates a significant dependence of states on intergovernmental transfers, and Canada lies as the middle of the road case with decentralized political institutions but with a tax revenue sharing system. Withing these political and fiscal institutions, evidence suggests that electoral competition, parties’ preferences over policy, the left and right ideology, and party alignment are important determinants of the size and composition of spending and taxation of subnational governments, the dependence of state and local governments on higher tiers of government, and the responsiveness of local authorities to the demands of residents.